Márkomeannu#2118, the Future is Already Here: Imagining a Sámi Future at the Intersection of Art and Activism - De Vivo, Erika (Text Matters: A Journal of Literature, Theory and Culture, 2022)
The 2018 edition of the Sámi festival Márkomeannu elaborated a narrative about the future of both the environment and society by articulating fears of an oncoming apocalypse and hopes for Indigenous Sámi futures through a concept presented to festivalgoers via site-specific scenography, visual narratives, and performances. This essay, addressing the festival as a site of artistic activism, reveals the conceptual bases and cultural significance of the festival-plot in relation to Indigenous Sámi cosmologies, the past and the possible future(s) in our time marked by escalating climate change. I argue that Márkomeannu-2018, providing a narrative about the future in which, amidst the Western societies’ dystopic colonial implosion, Indigenous people thrive, can be regarded as an expression of Indigenous Futurism. Counterpointing 19th-century theories predicting the imminent vanishing of Indigenous peoples while positioning the Sámi as modern Indigenous peoples with both a past and a future, this narrative constitutes an act of empowerment. Sámi history and intangible cultural heritage constituted repositories of meaning whereas a folktale constituted a framework for the festival-plot while providing an allegorical tool to read the present.